FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM PEMBELIAN CABAI RAWIT (STUDI KASUS: PASAR MANGKURAWANG DI KECAMATAN TENGGARONG) - Arista Damayanti; Syahrani; Defriansyah (Jurnal Magrobis, 2022)
Consumer behavior is the activities of individuals who are directly involved in obtaining and using goods and services, including the purchase decision-making process. The purpose of this study is to find out what factors influence consumer behavior in purchasing decisions of red chili peppers at Mangkurawang Market. The respondent selection technique used accidental sampling. With a sample of 40 respondents. The instrument test uses validity and reliability tests and the test results show valid and reliable. The analysis technique used is multiple linear regression, f test and t test. The results showed that the Cultural Factors, Social Factors, Personal and Psychological Factors partially had a significant effect on Consumer Behavior in Making Red Chili Rawit Purchase Decisions at Mangkurawang Market. Then Cultural Factors, Social Factors, Personal and Psychological Factors simultaneously have a significant effect on Consumer Behavior in Making Red Chili Pepper Purchase Decisions at Mangkurawang Market. Cultural Factors.